ED Formula, a Complex of Ecklonia cava and Chrysanthemum indicum, Ameliorates Airway Inflammation in Lipopolysaccharide-Stimulated RAW Macrophages and Ovalbumin-Induced Asthma Mouse Model - Hyun Kang; Chan-Hwi Park; Sang-Oh Kwon; Sung-Gyu Lee (Pharmaceuticals, 2023)
Ecklonia cava (E. cava) and Chrysanthemum indicum Linne (C. indicum) are natural raw materials known to have beneficial effects on inflammatory-related diseases, as evidenced by various sources in the literature. This study aimed to investigate the airway-protective effects of a formulation called ED, comprising E. cava and C. indicum, by evaluating its potential anti-inflammatory properties. Methods: The major components of ED were analyzed using high-performance liquid chromatography (HPLC) and its anti-inflammatory activity was assessed in RAW 264.7 cells through measurements of nitric oxide’s (NO) inhibitory effect, cyclooxygenase (COX)-2 protein expression, and the mitogen-activated protein kinase (MAPK) signaling pathway. Additionally, the anti-inflammatory effect of ED was evaluated in an ovalbumin-induced asthma model by measuring cytokine levels in serum, bronchoalveolar lavage fluid (BALF), and lung tissue. Through HPLC analysis, the major components of ED, dieckol and luteolin, were identified. ED demonstrated no cytotoxicity and effectively reduced NO production in lipopolysaccharide (LPS)-induced RAW 264.7 cells. Moreover, ED downregulated COX-2 expression through the MAPK signaling pathway in LPS-induced RAW 264.7 cells. In the ovalbumin-induced asthma model, the ED-treated group exhibited reduced levels of inflammatory cytokines in lung tissue. Furthermore, the ED-treated group showed a decrease in the number of inflammatory cells in BALF and lower serum interleukin (IL)-6 levels compared to the ovalbumin-treated group. These results suggest that ED has the potential to be a novel therapeutic agent for improving inflammatory respiratory diseases.